Service Design Capabilities - Morelli, Nicola; de Götzen, Amalia; Simeone, Luca (Springer Series in Design and Innovation,, 2021)
This open access book discusses service design capabilities in innovation processes, and provides a framework that guides design students, practitioners and researchers towards a better understanding of operational aspects of service design processes. More specifically, it revisits service designers' capabilities in light of the new roles that have opened up in innovation processes on different scales. After years of being inadequately defined, the professional profile of service designers is now taking shape. Today private and public institutions recognize service designers as essential contributors to their innovation and development processes. What are the capabilities that characterize a service designer? These essential capabilities are what service designers should acquire in their education and can sell when looking for a job.